A biosynthetic injectable adhesive and its preparation method and application in intestinal fistula repair
By developing a biological synthetic adhesive based on P (3HB-CO-3HA) materials, using optical cross-linking technology to solve the problem of lack of performance in the intestinal environment of existing adhesives, realized efficient and efficient, and efficient and efficient and efficient, Stable intestinal fistula repair.
Patent Information
- Application Number
- CN202410627810.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The existing bioadhesives have problems such as poor wet viscosity, impermis tolerance to digestive fluid corrosion, hard texture and allergic reactions in the intestinal environment, and cannot meet the requirements of intestinal fistula sealing and repairing at the same time.
A biosynthesis adhesive was developed, and a cluster (P (3HB-CO-3HA)) material (P (3HB-CO-3HA)) was used to use 3-hydroxyl-based but butycitic acid and medium and long-chain unsaturated hydroxyl fatty acids. The agent and solvents are solidified by the original position of optical cross -linked to form a biomitic synthetic adhesive with high adhesion, good flexibility, and anti -digestive liquid corrosion.
The rapid solidification and stable adhesion of the wet environment are realized, the risk of inflation is reduced, and the long -term stability and biocompatibility of the adhesive are guaranteed, and it is suitable for the repair of intestinal fistula.
Smart Images

Figure CN118576750B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a biosynthetic injectable adhesive and a preparation method thereof and application thereof in intestinal fistula repair. Background Art
[0002] Intestinal fistula refers to the pathological passage between the intestines, the intestines and other organs or the outside of the body, which causes the intestinal contents to flow out of the intestinal cavity, causing a series of pathological and physiological changes such as infection and organ dysfunction. The cause can be congenital developmental defects, or acquired inflammation, tumors, trauma and surgical complications. Among them, postoperative intestinal fistula is the most common, accounting for about 75% to 85% of all intestinal fistulas, and this type of intestinal fistula is often serious and complicated. It is a common emergency in gastrointestinal surgery, with an incidence of 2%-40%. The condition is critical and the mortality rate can be as high as 36%. It is one of the main causes of death in gastrointestinal surgery patients. The early symptoms are hidden, but the extravasation of digestive fluids can cause serious adverse reactions. Once the condition progresses, it deteriorates rapidly. The treatment time window is short and the treatment is difficult, which is a major problem faced by gastrointestinal surgeons.
[0003] Fistula is a key factor in the occurrence of intestinal fistula. The focus of intestinal fistula treatment is to try to close the fistula. In clinical practice, interventional therapy is usually used for fistulas that are difficult to heal on their own. In the early stage, surgical suture is generally performed, and when severe edema and abdominal adhesions occur, diversion enterostomy or intestinal resection is required. The treatment of fistulas by surgical suture is not only time-consuming and laborious, but also inevitably causes secondary damage to tissue puncture, increasing the risk of postoperative infection. Compared with traditional sutures, biological adhesives have many advantages such as easy use, time-saving operation, and prevention of postoperative complications. However, due to the presence of highly corrosive digestive fluids in the intestines, as well as a large amount of dynamic fluid exchange and secretion, higher special requirements are placed on the corrosion resistance and adhesion properties of the repair materials, resulting in restrictions on the application of adhesives. At present, there is no ideal biomaterial that can achieve ideal closure and repair of intestinal fistulas.
[0004] An ideal bioadhesive should meet the following requirements: 1) good biocompatibility and non-toxicity; 2) form a strong bond with moist tissue / organs; 3) suitable mechanical properties, adapted to the modulus of the tissue; 4) sufficient mechanical flexibility to withstand repeated dynamic mechanical forces applied by the tissue; 5) acceptable swelling properties to minimize tissue compression; 6) biodegradability, at a rate compatible with tissue healing. According to different sources, the various medical bioadhesives that have been developed can be roughly divided into two categories: 1) Natural sources: Typical adhesives of this type include fibrin sealants and gelatin-based sealants. Due to their natural origin, they have excellent biocompatibility, can support cell growth, and can be completely absorbed by tissues; 2) Artificial chemical synthesis: Typical adhesives of this type include cyanoacrylate glue (CA glue), which is a single-component tissue sealant synthesized from acrylaldehyde-based resin. It adheres and binds to the target surface within 5-6 seconds after contact with alkaline substances (such as water, blood, human tissue or moisture), and undergoes an exothermic polymerization reaction within 60 seconds to form a strong film. It is easy to use and has rapid bonding properties, and is widely used in medicine, industry and household activities. Among them, cyanoacrylate glue is widely used in medicine, industry and household activities because of its convenience and rapid bonding properties. However, due to its chemical synthesis, it has inherent defects such as poor biocompatibility, difficulty in degradation and toxic degradation products, and is generally only used for the closure of dry wounds. Compared with cyanoacrylate glue, fibrin glue has the following advantages: 1) non-toxic and biocompatible; 2) support cell growth; 3) can be completely absorbed by tissues; 4) the coagulation and degradation time of fibrin glue can be controlled. Although fibrin sealants have many advantages mentioned above, their limitations cannot be ignored: 1) some people have allergic reactions to them; 2) antibodies against fibrinogen and thrombin are formed, leading to coagulopathy and bleeding; 3) spread of infectious diseases; 4) cause systemic embolism; 5) poor mechanical strength.
[0005] In summary, all the bioadhesives used in clinical practice have more or less defects, such as poor wet adhesion, inability to resist digestive juice corrosion, hard texture, allergic complications, and cannot meet all the requirements of the application process at the same time. Therefore, it is urgent to develop a bioadhesive that is easy to use, has high adhesion in wet state, and is resistant to digestive juice corrosion to achieve the closure and repair of intestinal fistula. Summary of the invention
[0006] In view of the defects in the prior art, the present invention proposes a biosynthetic injectable adhesive and its preparation method and application in intestinal fistula repair. Specifically, the present invention utilizes the biological effects of the copolymer of 3-hydroxybutyric acid and medium-chain unsaturated hydroxy fatty acid monomers (P(3HB-co-3HA)) material for functional construction, and develops a biosynthetic injectable adhesive that is fast-curing, flexible, highly adhesive, resistant to digestive fluid corrosion, and has good biocompatibility and degradation properties. It is also convenient to combine with an endoscope for minimally invasive surgery, providing an innovative and efficient solution for intestinal fistula repair.
[0007] The present invention provides a biosynthetic injectable adhesive, which comprises component A, component B, component C, and component D;
[0008] The component A is a copolymer of 3-hydroxybutyric acid and medium- and long-chain unsaturated hydroxy fatty acid monomers;
[0009] The component B is a cross-linking agent, and the cross-linking agent is a dithiol compound;
[0010] The component C is a photoinitiator, and the photoinitiator is any one of 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl-2,4,6-trimethylbenzoyl lithium phosphite, benzoin dimethyl ether, and diphenyl ether;
[0011] The component D is a solvent, and the solvent is any one of ethyl acetate, tert-butyl alcohol, tetrahydrofuran, N,N-dimethylformamide, and acetone.
[0012] Furthermore, the chain length of the medium-chain unsaturated hydroxy fatty acid monomer is any one of eight to thirteen carbons.
[0013] Preferably, the chain length is any one of eight carbons, eleven carbons, and thirteen carbons.
[0014] Furthermore, the bis-thiol compound is any one of dithiothreitol and bis-thiol polyethylene glycol, wherein the molecular weight of the bis-thiol polyethylene glycol is any one of 200, 400, 1k, and 2k.
[0015] Preferably, the dithiol compound is dithiothreitol.
[0016] Furthermore, the molar percentage of the unsaturated hydroxy fatty acid monomer in component A is 10% to 99%, which can be 10%, 15%, 27%, 34%, 40%, 48%, 56%, 67%, 75%, 80%, 87%, 94%, 99%, and is preferably 40-70%.
[0017] Furthermore, the weight percentage of component A in the biosynthetic injectable adhesive is 10% to 80%, which can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, and preferably 20%-50%.
[0018] Furthermore, the weight percentage of component B in the biosynthetic injectable adhesive is 1% to 20%, which can be 1%, 2%, 3%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%, preferably 1%-5%.
[0019] Furthermore, the weight percentage of component C in the biosynthetic injectable adhesive is 0.01% to 2%, which can be 0.01%, 0.03%, 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.7%, 1%, 1.2%, 1.5%, 2%, and preferably 0.05%-0.5%.
[0020] The present invention also provides a method for preparing the biosynthetic injectable adhesive, which comprises the following steps:
[0021] (1) dissolving the component A in the component D to obtain a PHA gel precursor solution;
[0022] (2) Adding the component B and the component C to the PHA gelling precursor solution of step (1) to obtain a biosynthetic injectable adhesive.
[0023] The invention also provides application of the biosynthetic injectable adhesive in preparing soft tissue damage repair materials.
[0024] Furthermore, the soft tissue injury repair is preferably intestinal fistula repair.
[0025] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0026] 1. Compared with traditional adhesives that have the defect of failing adhesion due to swelling caused by absorption of body fluids, the biosynthetic injectable adhesive of the present application is tightly adhered to the tissue after in-situ curing through photo-crosslinking, and forms a hydrophobic organic gel network, which can effectively resist excessive swelling caused by infiltration of body fluids, reduce the risk of compression of surrounding tissues and nerves, weakening of adhesion and even adhesive shedding, and ensure its long-term stability during application.
[0027] 2. Compared with the mechanism of chemical covalent adhesion at the interface of traditional adhesives, the biosynthetic injectable adhesive of the present application achieves firm adhesion to substrates such as tissues through diffusion and topological entanglement mechanisms. This adhesion method, which does not rely on specific functional groups, has the potential to be applied on a variety of substrates and in different pH environments.
[0028] 3. Compared with traditional physical topological adhesives, the biosynthetic injectable adhesive of the present application is in situ cured by ultraviolet light-induced thiol-ene click reaction, achieving short-term rapid and robust adhesion in a wet environment, and introducing a covalent cross-linking network based on physical entanglement, thereby solving the problem of traditional physical topological adhesives taking a long time to reach peak adhesion and insufficient adhesion.
[0029] 4. Compared with traditional chemically synthesized adhesives, the biosynthetic injectable adhesive of the present application is prepared using unsaturated double bond P(3HB-co-3HA) material fermented by an engineered strain as raw material. Based on the inherent biological effects of the P(3HB-co-3HA) material, the biosynthetic injectable adhesive of the present application has excellent biosafety and degradation characteristics.
[0030] 5. Compared with traditional biological patch-shaped adhesives, the biosynthetic injectable adhesive of the present application is not only limited to sealing the outermost layer of the intestine, but also plays a stable closing role on the muscular layer and mucosal layer, and can adapt to various irregular shaped wounds. It can be combined with an endoscope for intestinal minimally invasive surgery, providing a new strategy for the occlusion and repair of intestinal fistulas. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 A synthetic route map and a schematic diagram of the adhesion mechanism of a biosynthetic injectable adhesive proposed in the present invention;
[0033] Figure 2 This is a physical picture of the biosynthetic injectable adhesive adhering to various tissues in Example 5 of the present invention;
[0034] Figure 3 This is a fluorescent image of the biosynthetic injectable adhesive penetrating fresh pig skin in Example 6 of the present invention;
[0035] Figure 4 is a graph of rheological properties of the biosynthetic injectable adhesive in Example 7 of the present invention;
[0036] Figure 5 This is a characterization diagram of the anti-swelling and digestive fluid corrosion resistance performance of the biosynthetic injectable adhesive in Example 8 of the present invention;
[0037] Figure 6 This is a graph characterizing the lap shear strength of the biosynthetic injectable adhesive in Example 9 of the present invention in different pH media and at different times underwater;
[0038] Figure 7 This is a characterization diagram of the interfacial adhesion ability of the biosynthetic injectable adhesive in Example 10 of the present invention;
[0039] Figure 8 This is a graph showing the in vitro sealing of the small intestine and the bursting pressure of the biosynthetic injectable adhesive in Example 11 of the present invention;
[0040] Fig. 9 Characterization of the cell compatibility of the biosynthetic injectable adhesive in Example 12 of the present invention;
[0041] Fig.10 This is a characterization diagram of the in vivo compatibility of the biosynthetic injectable adhesive in Example 13 of the present invention;
[0042] Fig.11 This is a diagram of the application of the biosynthetic injectable adhesive in Example 14 of the present invention in repairing in vivo colon defects. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.
[0044] The present invention is to synthesize a copolymer (P(3HB-co-3HA)) material of 3-hydroxybutyric acid and medium- and long-chain unsaturated hydroxy fatty acid monomers by biological fermentation of an engineering strain, and to form good adhesion with a variety of substrates by utilizing long-chain diffusion and topological entanglement. The chain segment diffusion ability of the P(3HB-co-3HA) material is further enhanced in a good solvent, has good wetting and penetration ability for tissue matrix, and can achieve rapid solidification of precursor solution and wound sealing by generating a thiol-ene click reaction with a dithiol compound under ultraviolet light irradiation conditions.
[0045] The thiol-ene click reaction between the active double bonds and the thiol groups initiated by ultraviolet light is a free radical polymerization reaction, and its reaction rate is closely related to the amount of the dithiol compound used. When the cohesive energy of the adhesive is insufficient, it will also lead to final bonding failure. The size of the cohesive energy is closely related to the double bond ratio in the medium- and long-chain unsaturated hydroxy fatty acid monomer (3HA) and the amount of the dithiol compound used. By adjusting the double bond ratio and the feed ratio of the dithiol compound, precise control of the curing time and the final bonding strength can be achieved.
[0046] Since the medium-chain P (3HB-co-3HA) material with unsaturated double bonds synthesized by biological fermentation of engineered strains has good biocompatibility and biodegradability, its degradation product 3-hydroxybutyric acid is a weakly acidic small molecule with little irritation to cells, and can promote cell proliferation and reduce inflammation to a certain extent. After the adhesive effectively seals the wound, the accompanying degradation of the material provides space for the growth of new tissue and accelerates tissue healing.
[0047] In summary, the synthetic route and adhesion mechanism of the biosynthetic injectable adhesive are as follows Figure 1 As shown, the biosynthetic injectable adhesive can still diffuse into the tissue and form topological entanglement in the presence of water, and quickly solidify within 10 seconds under ultraviolet light irradiation to form a firm seal and maintain a long-term high-strength adhesion effect.
[0048] Biosynthetic injectable adhesive and method for preparing the same:
[0049] Ingredients include:
[0050] (1) Component A is a copolymer of 3-hydroxybutyric acid and medium- and long-chain unsaturated hydroxy fatty acid monomers (P(3HB-co-3HA));
[0051] (2) Component B is a crosslinking agent / curing agent;
[0052] (3) Component C is a photoinitiator;
[0053] (4) Component D is a solvent.
[0054] Specifically, the chain length of the medium-chain unsaturated hydroxy fatty acid monomer (3HA) is any one of eight carbons to thirteen carbons. Preferably, the chain length of 3HA is eight carbons (C8 = ), 11 carbon (C11 = ) and 13 carbon (C13 = ) in any one of the above, the monomer can provide a reactive terminal double bond that can react.
[0055] The active terminal double bond ratio of P(3HB-co-3HAs) in the component A can be controllably adjusted by adjusting the ratio of different fermentation substrates, and the molar percentage (3HA mol%) of the medium-chain unsaturated monomer 3HA, i.e., the active terminal double bond ratio, is between 10% and 99%.
[0056] Preferably, the medium-chain unsaturated monomer 3HA is 11 carbon atoms (C11 = ) and when the 3HA mol% is 33%-99%, it is amorphous and sticky at room temperature, can form good adhesion with a variety of substrates through long-chain diffusion and topological entanglement, and provides sufficient active double bond sites for subsequent chemical modification.
[0057] Specifically, B in the component is a crosslinking agent / curing agent in the system, the crosslinking agent / curing agent is a bisthiol compound, the bisthiol compound is dithiothreitol (DTT), bisthiol polyethylene glycol (SH-(PEG) n -SH) wherein the molecular weight of the bismercaptoethylene glycol is any one of 200, 400, 1k, and 2k.
[0058] Preferably, the component B is DTT.
[0059] Specifically, the component C is a photoinitiator, and the photoinitiator is any one of 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl-2,4,6-trimethylbenzoyl lithium phosphite, benzoin dimethyl ether, and diphenyl ether.
[0060] Specifically, the component D is a solvent, and the solvent is any one of ethyl acetate, tert-butyl alcohol, tetrahydrofuran, N,N-dimethylformamide, and acetone.
[0061] Preferably, the component D is ethyl acetate and tert-butyl alcohol, which are green solvents in the pharmaceutical manufacturing industry.
[0062] The specific preparation method comprises the following steps:
[0063] (1) dissolving component A in component D to obtain a PHA gel precursor solution;
[0064] (2) adding a certain mass fraction of component B and component C to the above-mentioned precursor solution to form the biosynthetic injectable adhesive;
[0065] Preferably, the method is as follows:
[0066] Component A 3HA mol% is 40% C11 =The component D is dissolved in ethyl acetate as a PHA gel precursor, and a crosslinker DTT and a photoinitiator 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone are added thereto to form the biosynthetic injectable adhesive. The subsequent examples use the preferred method (Example 1) to prepare the biosynthetic injectable adhesive for performance verification experiments.
[0067] In any embodiment of the present application, the molar percentage of the unsaturated hydroxy fatty acid monomer in component A is 10% to 99%, preferably 40% to 70%.
[0068] In any embodiment of the present application, the weight percentage of component A in the biosynthetic injectable adhesive is 10% to 80%, preferably 20% to 50%.
[0069] In any embodiment of the present application, the weight percentage of component B in the biosynthetic injectable adhesive is 1% to 20%, preferably 1% to 5%.
[0070] In any embodiment of the present application, the weight percentage of component C in the biosynthetic injectable adhesive is 0.01% to 2%, preferably 0.05% to 0.5%.
[0071] Example 1
[0072] A method for preparing a biosynthetic injectable adhesive comprises the following steps:
[0073] Component A 3HA mol% is 40% C11 = (500 mg) was dissolved in component D ethyl acetate (1 mL) as a PHA gel precursor solution, and a crosslinking agent DTT (10 mg) and a photoinitiator 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (5 mg) were added thereto to form the biosynthetic injectable adhesive.
[0074] Among them, the molar percentage of unsaturated hydroxy fatty acid monomer in component A is 40%, the weight percentage of component A in the biosynthetic injectable adhesive is 50%, the weight percentage of component B in the biosynthetic injectable adhesive is 1%, and the weight percentage of component C in the biosynthetic injectable adhesive is 0.5%.
[0075] Example 2
[0076] A method for preparing a biosynthetic injectable adhesive comprises the following steps:
[0077] Component A 3HA mol% C8= (800 mg) with 99% mol% was dissolved in component D ethyl acetate (1 mL) as a PHA gel precursor, and 200 mg of a crosslinking agent (bis-mercapto polyethylene glycol with a molecular weight of 2000) and a photoinitiator benzoin dimethyl ether (20 mg) were added thereto to form the biosynthetic injectable adhesive.
[0078] Among them, the molar percentage of unsaturated hydroxy fatty acid monomer in component A is 99%, the weight percentage of component A in the biosynthetic injectable adhesive is 80%, the weight percentage of component B in the biosynthetic injectable adhesive is 20%, and the weight percentage of component C in the biosynthetic injectable adhesive is 2%.
[0079] Example 3
[0080] A method for preparing a biosynthetic injectable adhesive comprises the following steps:
[0081] Component A 3HA mol% C13= (100 mg) with 10% mol% was dissolved in component D tert-butyl alcohol (1 mL) as a PHA gel precursor, and 50 mg of a cross-linking agent (bis-mercapto polyethylene glycol with a molecular weight of 400) and a photoinitiator phenyl-2,4,6-trimethylbenzoyl lithium phosphite (0.1 mg) were added thereto to form the biosynthetic injectable adhesive.
[0082] Among them, the molar percentage of unsaturated hydroxy fatty acid monomer in component A is 10%, the weight percentage of component A in the biosynthetic injectable adhesive is 10%, the weight percentage of component B in the biosynthetic injectable adhesive is 5%, and the weight percentage of component C in the biosynthetic injectable adhesive is 0.01%.
[0083] Example 4 Application of biosynthetic injectable adhesive
[0084] The biosynthetic injectable adhesive described in the present application can be used for bonding and sealing soft tissues such as skin and intestines. The specific method is: injecting the photoinduced biosynthetic injectable adhesive into the tissue wound site, and irradiating it under 365nm ultraviolet light for 5 seconds to 1 minute to form a gel to achieve wound sealing.
[0085] Example 5 Qualitative Characterization of Biosynthetic Injectable Adhesion to Multiple Tissues
[0086] The biosynthetic injectable adhesive in the present application can be injected between the tissue surface and a glass slide coated with gelatin (20% (w / w)) (simulating skin and facilitating light transmission), and form a strong bond between the two substrates within 1 minute of UV irradiation. Figure 2 As shown, the biosynthetic injectable adhesive exhibits good adhesion properties to heart, liver, spleen, lung, large intestine and small intestine tissues.
[0087] Example 6 Characterization of the penetration ability of biosynthetic injectable adhesive into fresh pig skin
[0088] To test the tissue penetration ability of the biosynthetic injectable adhesive of the present invention, wet pig skin was selected as the model tissue because the mechanical and biological properties of wet pig skin are similar to those of human skin. The injectable adhesive precursor solution (CLC11) containing 6-aminofluorescein (6-AF, excitation wavelength 490nm) was = ) and placed on the surface of fresh pig skin (2×2cm 2 ), and at specific time points, the adhesive-tissue assemblies were imaged using confocal laser scanning microscopy to measure the depth of adhesive penetration over time. Commercial cyanoacrylate glue (CA glue) was set as a control group. Figure 3 As shown, the penetration depth of the biosynthetic injectable adhesive in pig skin increases with time, reaching about 800 μm in 5 minutes, far exceeding the penetration depth of commercial CA glue, breaking through the limitation of CA glue in wet bonding (low permeability caused by rapid anionic polymerization triggered by water). The positive correlation between the above penetration depth and penetration time confirms that the biosynthetic injectable adhesive has good penetration ability into tissue substrates and can form a topological entanglement network with tissues.
[0089] Example 7 Rheological Properties of Biosynthetic Injectable Adhesives
[0090] To test the injectability, gelation time and structural stability of the biosynthetic injectable adhesive in this application. All rheological measurements were performed on a rheometer (MCR 301, Anton Paar) using a plate with a diameter of 8 mm. Viscosity measurements were performed under a fixed constant strain of 1% and a shear rate range of 0.01-100 s -1 ; Oscillation time sweep measurements were performed at a fixed strain of 1.0% and a frequency of 1 Hz; frequency sweep measurements were performed at a fixed constant strain of 1% and a frequency range of 0.1-10 Hz; amplitude sweep measurements were performed at a fixed frequency of 1 Hz and a strain range of 0.1-1000%; all test temperatures were maintained at 37 °C and the normal stress F N is 0N. Figure 4 As shown in a, the injectable adhesive exhibits a "shear thinning" phenomenon, has good injectability, and is easy to contact with various irregular tissue substrates and quickly wet and penetrate; Figure 4 As shown in b, the injectable adhesive can undergo photo-crosslinking within 5 seconds under ultraviolet light irradiation, has the ability to cure rapidly, and can quickly cure and form a firm seal after contacting tissue under light; Figure 4As shown in c, after the injectable adhesive is cured into a gel, its modulus remains fairly constant in the frequency range of 0.1-10 Hz (this interval includes and exceeds the range of activity of the small intestine), demonstrating the viscoelasticity and long-term network stability of the biosynthetic injectable adhesive after gelation; and this structural stability Figure 4 This is further demonstrated in Figure d, where the data show that the biosynthetic injectable adhesive has a broad linear viscoelastic region with a yield network fracture strain exceeding 700%, all of which indicate that the biosynthetic injectable adhesive can withstand large deformations / strains and is "fracture-resistant" within the desired application range (anastomosis surgery and postoperative in vivo joint movement).
[0091] Example 8 Characterization of the anti-swelling and digestive fluid corrosion resistance of biosynthetic injectable adhesive
[0092] In this embodiment, the biosynthetic injectable adhesive after gelation is placed in centrifuge tubes containing phosphate buffered saline (PBS) and artificial simulated intestinal fluid (SIF), and placed in a shaker for incubation (37°C, 300rpm). Samples are taken out at specific time points, and the excess water is absorbed from the surface, and then weighed and photographed for record. The definition of swelling ratio (%) is Swelling Ratio (%) = (m1-m0 / m0) × 100%, where m1 is the mass of the sample after swelling at a given time point, and m0 is the initial mass of the sample. Figure 5 As shown, after the biosynthetic injectable adhesive after gelling was immersed in PBS for 72 hours, the surface morphology shrank slightly and turned white, while the quality remained constant during the immersion process, indicating that the biosynthetic injectable adhesive of the present application has excellent anti-swelling properties; the biosynthetic injectable adhesive after gelling only swelled slightly when immersed in SIF, and reached swelling equilibrium within 4 hours (swelling rate was 8.31%). Scanning electron microscopy observation of its cross-section revealed that the interior of the biosynthetic injectable adhesive after gelling was originally a dense gel network, and a small amount of pore structure appeared after immersion in SIF. These experimental phenomena indicate that the biosynthetic injectable adhesive of the present application has good resistance to corrosion by digestive fluid.
[0093] Example 9 Characterization of lap shear strength of biosynthetic injectable adhesive in different pH media and under water for different time periods
[0094] In order to test the adaptability of the biosynthetic injectable adhesive in the present application to different pH media environments and the long-term underwater adhesion stability. In this example, the biosynthetic injectable adhesive was tested according to the revised ASTM F2255-05 tissue adhesive lap shear strength standard. Two glass slides (25mm×75mm) were used to store the samples. A gelatin solution (20% w / w) was applied to the top of the glass slide (10mm×15mm) and dried at room temperature to obtain a glass slide coated with gelatin (to simulate skin and facilitate light transmission). The biosynthetic injectable adhesive precursor solution CLC11 was added to the sample. = (20 μL) was added to the gelatin coating area of the two glass slides and irradiated under ultraviolet light for 5 seconds for photocrosslinking. The two glass slides that had undergone photocrosslinking were immersed in water and medium liquids of different pH values (pH = 3, 7, 9, and 11), taken out at specific time points, and subjected to lap shear tests using a universal mechanical testing machine at a strain rate of 1 mm / min. Commercial cyanoacrylate glue (CA glue) was set as the control group. The shear strength of the biosynthetic injectable adhesive was measured at the separation point as shown in Figure 2. Figure 6 As shown, after immersion in water or in different pH media for 24 hours, the lap shear strength of the biosynthetic injectable adhesive of the present application decreased to a certain extent, but it was still able to maintain a relatively high strength (about 400 kPa), which is significantly higher than commercial CA glue (about 5 kPa), demonstrating its advantages over CA glue in various wet environments, indicating that the biosynthetic injectable adhesive of the present application has the potential to be used in wet environments of different pH in vivo.
[0095] Example 10 Characterization of 90° Peel Strength of Biosynthetic Injectable Adhesive
[0096] In order to test the interfacial adhesion of the biosynthetic injectable adhesive on the intestinal tissue in this application, the biosynthetic injectable adhesive in this example was tested for its 90° peel strength on the pig intestine using a texture analyzer. The pig intestine standard sample size was 60 mm × 15 mm. = (50μL) was injected into the outer surface of the pig intestine and fixed on a slide coated with gelatin. After incubation in a humid environment for 3 minutes, the sample was irradiated with ultraviolet light for 5s to complete the sample preparation. The peeling test was carried out at a speed of 10mm / min. Commercial cyanoacrylate glue (CA glue) was set as the control group. According to the elastic peeling theory, the interfacial adhesion energy is determined by G=F / d, where F is the average value of the peeling force and d is the width of the adhesion area. (n≥30). Figure 7 As shown in Figure 2, the energy of the biosynthetic injectable adhesive when peeled off from the outer surface of pig intestine reached 406.78 J / m 2 , which is higher than the peeling energy of commercial CA glue (about 128.45J / m 2), indicating that the biosynthetic injectable adhesive of the present application has excellent interfacial adhesion ability to intestinal tissue.
[0097] Example 11 In vitro sealing of the small intestine and characterization of burst pressure of biosynthetic injectable adhesive
[0098] In order to test the viscosity and stability of the biosynthetic injectable adhesive in the present application in sealing intestinal tissue under pressure. The bursting pressure of the biosynthetic injectable adhesive in this embodiment was tested according to the revised ASTM F2392-04 standard. A section of pig intestine (about 8 cm) and a pressure gauge were connected to the injection pump through a plastic tube, and a 4 mm diameter defect was made on the surface of the pig intestine using a punch. 50 μL of the precursor solution CLC11 of the biosynthetic injectable adhesive was injected into the injection pump. = Injected into the defect site, the tissue was sealed after 5s of ultraviolet light exposure. During the test, air was compressed into the pig intestine at a rate of 0.1mL / s through a syringe, and the peak pressure recorded after rupture was the burst pressure (n=3). Commercial cyanoacrylate glue (CA glue) was set as the control group. Figure 8 As shown in the figure, the bursting pressure of the biosynthetic injectable adhesive on the pig intestine is about 158.67 mmHg, while the bursting pressure of the commercial CA glue is about 23 mmHg, which is almost consistent with the maximum pressure of the healthy intestine (about 20 mmHg). Furthermore, the adhesion stability of the biosynthetic injectable adhesive was tested by simulating the moist environment of the intestine in vitro sealed intestinal perforation experiment. A hole with a diameter of 5 mm was made on the surface of the pig intestine with a punch, and 100 μL of the biosynthetic injectable adhesive precursor CLC11 was injected into the pig intestine. = The defect was injected and the tissue was sealed after irradiation with ultraviolet light for 30 seconds. The sealed pig intestine was then immersed in PBS buffer and filled with artificial simulated intestinal fluid SIF (pH = 6.8, in order to obtain a better visual effect, the red dye Alizarin red was used to dye SIF). Figure 8 As shown, the biosynthetic injectable adhesive can achieve a firm seal of intestinal perforation for 48 hours under conditions of simulated intestinal humid environment, while the commercial CA glue leaked after 4 hours. These data indicate that the biosynthetic injectable adhesive of the present application has excellent sealing ability and long-term stability for intestinal tissue under pressure.
[0099] Example 12 Characterization of Cytocompatibility of Biosynthetic Injectable Adhesive
[0100] In this example, intestinal epithelial cells IECs were used as model cells to evaluate the cytotoxicity of the biosynthetic injectable adhesive. =After sterilization, the coating was evenly applied to the bottom of the cell culture plate and cured under ultraviolet light for 30 seconds to obtain a biosynthetic injectable adhesive coating with a thickness of about 300 μm. Cells were inoculated on the coating for culture (inoculation density was 3000 cells / well), and directly inoculated on a blank plate as a control. After incubation in a carbon dioxide incubator for 72 hours, the cell viability was tested using live / dead cell fluorescence staining. The live / dead cell staining photos show Fig. 9 As shown in the figure, almost no dead cells were observed in the presence or absence of biosynthetic injectable adhesive. Further, the cell proliferation was tested and statistically analyzed using the CCK-8 cell viability detection kit, and it was found that the survival rate of IECs cells in the presence of biosynthetic injectable adhesive was higher than 100% (as shown in the figure). Fig. 9 As shown), this indicates that the biosynthetic injectable adhesive has good biocompatibility and no obvious cytotoxicity.
[0101] Example 13 In vivo compatibility characterization of biosynthetic injectable adhesive
[0102] In order to demonstrate the in vivo compatibility of the biosynthetic injectable adhesive of the present application, an in vivo implantation experiment of an animal model was conducted in this example. The results are as follows: Fig.10 As shown. Fig.10 As shown in a, rats were used as experimental subjects to conduct an inflammatory response test of subcutaneous biosynthetic injectable adhesive implanted on the back. After 1 week and 4 weeks of implantation, the full-thickness skin tissue and organ tissue around the implanted samples were collected for pathological analysis, and blood was collected by cardiac puncture from the rats for blood analysis to evaluate the safety of the biosynthetic injectable adhesive's in vivo metabolism. Fig.10 As shown in the HE staining results in c, the implanted samples did not cause inflammatory reactions in the surrounding skin tissues, and no obvious inflammatory lesions or signs of damage were observed in key organ tissues. Fig.10 As shown in the blood analysis results in b, the blood analysis results of the animals with subcutaneous implantation of the samples are comparable to those of healthy animals, indicating that the biosynthetic injectable adhesive of the present application has excellent biocompatibility.
[0103] Example 14 Application of biosynthetic injectable adhesive for repairing colon defects in vivo
[0104] In order to demonstrate the effect of the biosynthetic injectable adhesive of the present application on intestinal perforation repair in vivo, an animal colon defect model was tested in this example. The results are shown in FIG. Fig.11 As shown. Fig.11As shown in a, an intestinal perforation model (5 mm in diameter) was established in the rat colon, and the perforation site was sealed and repaired using sutures, commercial cyanoacrylate glue (CA glue), and biosynthetic injectable adhesive, respectively. The repair of colon perforation was observed fourteen days after surgery. Fig.11 As shown in a, there was no intestinal leakage or infection in the rats in each group. The commercial CA glue group had severe tissue adhesion and tissue sclerosis at the defect site. In contrast, the suture group and the biosynthetic injectable adhesive group had only a small amount of tissue adhesion, but the colon wall edema was obvious and the colon tube was dilated in the suture group.
[0105] The repair effect of the biosynthetic injectable adhesive was evaluated by pathological staining of colon tissue at the experimental site. Fig.11 As shown in Fig. b, the defect site of the commercial CA glue group had disordered structure and slow healing; the defect site of the suture group had obvious changes and poor arrangement of the mucosa and muscular layer, lack of mucosal glandular tissue and submucosal hematoma (related to acupuncture); in contrast, the defect site of the biosynthetic injectable adhesive was basically filled with muscular mucosal tissue, and although there was no surface mucosal glandular tissue, complete closure was achieved. In addition, PAI-1 and PA immunohistochemistry were used to evaluate the degree of colon tissue fibrosis, and the results were shown in Fig. Fig.11 c. PAI-1 is a serine protease inhibitor induced by TGF-β1, which promotes intestinal fibrosis and myofibroblast gene expression; PA stimulates fibrinolytic intestinal fibrosis by activating plasminogen reduction. According to the staining results, compared with the suture group and the commercial CA glue group, the PAI-1 expression in the biosynthetic injectable adhesive group of the present application was significantly reduced and the PA expression was significantly increased. Compared with sutures and commercial CA glue, the biosynthetic injectable adhesive of the present application exhibits good sealing ability, biocompatibility and a certain ability to prevent postoperative adhesions, which indicates that the biosynthetic injectable adhesive in the present invention has the potential to effectively block and repair intestinal fistulas.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A biosynthetic injectable adhesive, characterized in that: The biosynthetic injectable adhesive comprises component A, component B, component C, and component D; The component A is a copolymer of 3-hydroxybutyric acid and medium- and long-chain unsaturated hydroxy fatty acid monomers; The component B is a cross-linking agent, and the cross-linking agent is a dithiol compound; The component C is a photoinitiator, and the photoinitiator is any one of 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl-2,4,6-trimethylbenzoyl lithium phosphite, benzoin dimethyl ether, and diphenyl ether; The component D is a solvent, and the solvent is any one of ethyl acetate, tert-butyl alcohol, tetrahydrofuran, N,N-dimethylformamide, and acetone.
2. The biosynthetic injectable adhesive according to claim 1, characterized in that The chain length of the medium-chain unsaturated hydroxy fatty acid monomer is any one of eight to thirteen carbons.
3. The biosynthetic injectable adhesive according to claim 1, characterized in that: The bis-mercapto compound is any one of dithiothreitol and bis-mercapto polyethylene glycol, wherein the molecular weight of the bis-mercapto polyethylene glycol is any one of 200, 400, 1k, and 2k.
4. The biosynthetic injectable adhesive according to claim 2, characterized in that: The molar percentage of the unsaturated hydroxy fatty acid monomer in component A is 10%-99%.
5. The biosynthetic injectable adhesive according to claim 1, characterized in that: The weight percentage of component A in the biosynthetic injectable adhesive is 10% to 80%.
6. The biosynthetic injectable adhesive according to claim 1, characterized in that The weight percentage of component B in the biosynthetic injectable adhesive is 1%-20%.
7. The biosynthetic injectable adhesive according to claim 1, characterized in that: The weight percentage of the component C in the biosynthetic injectable adhesive is 0.01%-2%.
8. The method for preparing the biosynthetic injectable adhesive according to claim 1, characterized in that: The preparation method comprises the following steps: (1) dissolving the component A in the component D to obtain a PHA gel precursor solution; (2) Adding the component B and the component C to the PHA gelling precursor solution of step (1) to obtain a biosynthetic injectable adhesive.
9. Use of the biosynthetic injectable adhesive according to any one of claims 1 to 7 in the preparation of soft tissue damage repair materials.
10. The use according to claim 9, characterized in that: The soft tissue injury repair is intestinal fistula repair.
Citation Information
Patent Citations
Collagen modified poly(3-hydroxybutyrate-3-hydroxyvalerate) and its preparing method and application
CN101012306A
Amphiphilic bio-based degradable underwater adhesive as well as preparation method and application thereof
CN112409974A